Did British women achieve long-term economic benefits from working in essential WWII industries? - Robert A. Hart (Institute for the Study of Labor (IZA), 2009)
Between mid-1939 and mid-1943 almost 2.2 million additional women were recruited into Britain's essential war industries. These consisted, predominantly, of young women recruited into metal and chemical industries. Much of the increased labour supply was achieved through government directed labour initiatives. This culminated, in January 1942, with the Control of Engagement Order whereby women between the ages of 18 and 40 who either entered the labour market or who changed employment were compulsorily directed into jobs and industries that were vital to the war effort. There were also many woman volunteers for such work, partly due to the fact that extreme labour scarcity drove up relative female wage rates. At least 42% of the 18-20 age cohorts and 32% of the 21-25 age cohorts in 1943 worked in the essential industries. Two-thirds of those involved owed their jobs to wartime industrial expansion. The majority of such women entered a world of work that had been previously dominated by men. They obtained considerable training, job experience and pay advantages compared to subsequent age cohorts who were not eligible for war work. This bestowed on them subsequent labour market advantages that would otherwise not have occurred. Using a regression discontinuity design the empirical work shows that the long term earnings benefits of those age cohorts eligible for conscription, measured 30 years after the war, were in the order of between 2% and 9% higher than the age cohorts that followed them.
urn:nbn:de:101:1-20090304361
Keywords: J16; J24; J31; N44; 330; WWII female employment; essential war industries; long-term real wages; regression discontinuity design; Frauenerwerbstätigkeit; Kriegswirtschaft; Rüstungsindustrie; Einkommen; Reallohn; Kohortenanalyse; Großbritannien